2002
DOI: 10.1093/emboj/21.4.546
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin is essential for survival during membrane stress in Candida albicans

Abstract: The immunosuppressants cyclosporin A (CsA) and FK506 inhibit the protein phosphatase calcineurin and block T-cell activation and transplant rejection. Calcineurin is conserved in microorganisms and plays a general role in stress survival. CsA and FK506 are toxic to several fungi, but the common human fungal pathogen Candida albicans is resistant. However, combination of either CsA or FK506 with the antifungal drug¯uconazole that perturbs synthesis of the membrane lipid ergosterol results in potent, synergistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
309
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(337 citation statements)
references
References 104 publications
19
309
0
2
Order By: Relevance
“…62,71,72 These in vitro results are supported by gene deletion studies showing that calcineurin-defective C. albicans mutants were more sensitive to stress conditions than isogenic wild-type controls, were markedly hypersensitive to azoles, and had attenuated virulence in mice with systemic candidiasis. [73][74][75] Although that hypovirulence is attributed to sensitivity of C. albicans to killing by serum mediated by Ca 2+ , no reported data have indicated that pharmacological inhibition of calcineurin also protects against calcium stress. Interestingly, loss of function crz1 C. albicans mutants, defective in crz1 which encoded a downstream transcription effector of the calcineurin, Crz1, were not sensitive to serum and exhibited no decrease in virulence.…”
Section: Inhibitors Of Calcineurin and Tormentioning
confidence: 99%
See 1 more Smart Citation
“…62,71,72 These in vitro results are supported by gene deletion studies showing that calcineurin-defective C. albicans mutants were more sensitive to stress conditions than isogenic wild-type controls, were markedly hypersensitive to azoles, and had attenuated virulence in mice with systemic candidiasis. [73][74][75] Although that hypovirulence is attributed to sensitivity of C. albicans to killing by serum mediated by Ca 2+ , no reported data have indicated that pharmacological inhibition of calcineurin also protects against calcium stress. Interestingly, loss of function crz1 C. albicans mutants, defective in crz1 which encoded a downstream transcription effector of the calcineurin, Crz1, were not sensitive to serum and exhibited no decrease in virulence.…”
Section: Inhibitors Of Calcineurin and Tormentioning
confidence: 99%
“…This interaction extends to the other azoles as well as terbinafine and was observed in both susceptible C. albicans and azole-resistant species, including C. glabrata. [71][72][73] Checkerboard microdilution and time-kill experiments found that at a concentration of 0.625 μg/ ml (i.e., at a concentration achievable in vivo), CsA was synergistic with fluconazole, reducing viable Candida counts by 2 logs. 77 Importantly, testing of Candida isolates obtained from liver transplant recipients receiving tacrolimus showed that treatment with this agent did not select for resistance toward calcineurin inhibitors.…”
Section: Inhibitors Of Calcineurin and Tormentioning
confidence: 99%
“…Cells were grown in YPD medium containing 1% yeast extract (Difco Laboratories, Detroit, MI, USA), 2% Bacto-peptone (Difco Laboratories) and 2% glucose at 30 1C with vigorous shaking. Unless stated otherwise, cells from the overnight-grown culture were collected by centrifugation, washed twice with RPMI 1640 medium with L-glutamine (RPMI 1640 medium), 18 and suspended in the same medium to obtain a final cell density of 1Â10 7 cells ml À1 . Cells were then incubated in the absence or presence of each compound with vigorous shaking at 37 1C.…”
Section: Measurement Of Cell Growth and Viabilitymentioning
confidence: 99%
“…CaIPF14030 is overexpressed during the stepwise acquisition of azole resistance in DSY1024 It has been well documented that calcium can activate the calcineurin pathway and modulate azole activity in C albicans [22,23] . Because the CaIPF14030 gene of C albicans is up-regulated by Ca 2+ in a calcineurin-dependent manner, we investigated the dynamic expression of CaIPF14030 in the DSF7, DSF14, DSF21, and DSF28 strains obtained in our previous study [18] .…”
Section: Resultsmentioning
confidence: 99%
“…CaIPF14030 was up-regulated by Ca 2+ in a calcineurin-dependent manner. It is well documented that calcium can activate the calcineurin pathway and modulate azole activity in C albicans [22,23] . In addition, the dynamic expression of CaIPF14030 was investigated in the DSF7, DSF14, DSF21, and DSF28 strains obtained in our previous study [18] .…”
Section: Discussionmentioning
confidence: 99%